INTEREST OF INTERMEDIATE COLLEGE STUDENTS ON VOCATIONAL COURSES (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Vocational interest is defined as one’s own pattern of preferences aptitudes, likes and dislikes, preferred in any manner, wisely or unwisely by self or by another source for a given vocational area or vocation. Therefore, the importance of the study of the present record is to help students to adjust themselves to the careers or jobs or vocations by making wise choices. Only by making right choice the student will be able to utilize his all the potentialities to the maximum extent.  Thus the main importance of the study of the VIR is to measure vocational interests, to enable to pupils to select such subjects in schools which are according to their preferred vocations.    Hence the researcher proposed to study on the topic, vocational interest of degree college students.